Reef Fishes Colonization Rate Around Artificial Reef in Putus-putus Island, South-East Minahasa District - Laurentius T. X. Lalamentik; Unstain N. W. J. Rembet; Adnan S. Wantasen (Jurnal Ilmiah PLATAX, 2017)
A comprehensive research effort was directed to increase the ecological role of Putus-Putus island coral reefs. This study was an implementation of artificial reef technology as fish colonization locality. The artificial reefs were made of 20x20x100 cm-concrete blocks placed in 6 levels and located at the depth of 8-10 m. Reef fish observations were done three times in two locations. Environmental parameters, such as temperature, salinity and visibility, were also measured. Environmental parameters (temperature, salinity a. Water temperature (29.65oC and 29.64oC) supported the coral growth as well. Salinity distribution  was not significantly different among the study sites.  This study also found 37 reef fish species belonging to 18 families. Number of species varied with observed time and localities. Total number of individuals increased with number of fish species. Mean number of individuals and species of reef fish in locality B were higher than those in locality A. Moreover, the reef fish colonization rate in the study site followed the model y = 4.3801e0.5249x with R2= 0.9297 in the strait and y = 5.0397e0.5493x  with R2= 0.9297 for the Bay. Keywords: Artificial reefs, reef fish. Abstrak Suatu upaya penelitian yang komprehensif diarahkan untuk peningkatan fungsi ekologi terumbu karang Pulau Putus-Putus. Penelitian ini berupa penerapan teknologi terumbu buatan sebagai tempat hunian ikan. Terumbu buatan terbuat dari balok cor beton berukuran 20x20x100 cm bersusun 6 dan ditempatkan pada kedalaman 8-10 m. Pengamatan ikan karang dilakukan 3 kali di 2 lokasi berbeda. Parameter lingkungan, seperti suhu, salinitas, dan kecerahan, juga diukur.    Hasil pengukuran yang diperoleh (29,65 oC dan 29,64 oC) termasuk suhu yang optimal untuk pertumbuhan karang. Dari hasil penelitian, ditemukan 37 spesies yang masuk dalam 18 famili ikan karang. Jumlah spesies yang ditemukan bervariasi pada setiap waktu dan lokasi pengamatan. Pengambilan spesies ikan karang dilakukan pada 2 lokasi dengan masing-masing lokasi dilakukan 3 kali pengambilan sampel. Berdasarkan hasil yang diperoleh (tabel 03) dapat dilihat bahwa jumlah individu bertambah seiring dengan banyaknya jumlah spesies ikan karang yang didapat. Rata-rata jumlah individu dan jumlah spesies ikan karang pada lokasi B lebih banyak. Laju hunian ikan karang di lokasi penelitian mengikuti model y = 4.3801e0.5249x dengan R2= 0,9297 untuk lokasi Selat dan y = 5.0397e0.5493x  dengan R2= 0,9297 untuk lokasi Teluk. Kata kunci : Terumbu buatan, ikan karang